Aerobic H2 production related to formate metabolism in white-rot fungi - Mori, Toshio; Takahashi, Saaya; Soga, Ayumi; Arimoto, Misa; Kishikawa, Rintaro; Yama, Yuhei; Dohra, Hideo; Kawagishi, Hirokazu; Hirai, Hirofumi (Frontiers in Fungal Biology, 2023)
Biohydrogen is mainly produced by anaerobic bacteria, anaerobic fungi, and algae under anaerobic conditions. In higher eukaryotes, it is thought that molecular hydrogen (H2) functions as a signaling molecule for physiological processes such as stress responses. Here, it is demonstrated that white-rot fungi produce H2 during wood decay. The white-rot fungus Trametes versicolor produces H2 from wood under aerobic conditions, and H2 production is completely suppressed under hypoxic conditions. Additionally, oxalate and formate supplementation of the wood culture increased the level of H2 evolution. RNA-seq analyses revealed that T. versicolor oxalate production from the TCA/glyoxylate cycle was down-regulated, and conversely, genes encoding oxalate and formate metabolism enzymes were up-regulated. Although the involvement in H2 production of a gene annotated as an iron hydrogenase was uncertain, the results of organic acid supplementation, gene expression, and self-recombination experiments strongly suggest that formate metabolism plays a role in the mechanism of H2 production by this fungus. It is expected that this novel finding of aerobic H2 production from wood biomass by a white-rot fungus will open new fields in biohydrogen research.